Modification of the sentencing of transgender convict - Maya Shafira; Hasnaa Niditya Rosyaadah; Emilia Susanti; Gunawan Jatmiko; Damanhuri Warganegara (Institute for Advanced Science, Social, and Sustainable Future, 2023)
The existence of transgender people in Indonesia cannot be accepted by society because they are considered to deviate from existing cultural values. Their status as transgender also makes it difficult to place them in correctional institutions when someone commits a crime. There is no legal certainty and there is a legal vacuum so that there is a need for criminal law modifications such as alternative punishments outside of prison for transgender inmates. This study has two aims: First to find out criminal modifications in the current punishment of transgender inmates, Second to that describe the concept of ideal criminal modification for transgender inmates. this study uses a normative juridical and empirical juridical approach with data collected through literature studies and field studies. The conclusion is there is a need for modifications in the criminal system, such as the placement of transgender prisoners as seen from their identification cards such as ID cards or passports, as well as court decisions if they have applied for a sex change and it has been legalized. In addition, alternative punishments other than imprisonment for transgender convicts can provide legal certainty for them in order to avoid a legal vacuum. Alternative punishment also serves to protect prisoners from the possibility of bullying and harassment for transgender prisoners.